THE DEVELOPMENT OF TRANSPORT INFRASTRUCTURE AND NIGERIA’S COLONIAL ECONOMY.1892 - 1960 - Okeke Ugochukwu Ahizechukwu (International Studies Journal)
ABSTRACT Transport infrastructure had existed in Nigeria before the British effective occupation of what later became Nigeria.The ethnic fragments that made up the country existed politically independent of each other and they engaged in some form of economic relationships with other trading partners outside the country before the British dominated the colonial economy. The colonial economy and transport infrastructure therefore was structured in a way that benefitted the handlers. The objective of this work is to understand the nexus between transport infrastructure and Nigeria’s colonial economy upto the 1960, as the British colonialist developed the country’s transport infrastructure to aid economic exploitation and export. The work gives a historical background to Nigeria’s colonial system of administration and the colonial economy before the advent of the colonialism. It further examines the role of transport infrastructure on Nigeria’s colonial economy as a result of the influence of British colonialists that dominated the colonial economy. The methodology of this work is based on secondary sources of information. This work therefore gives a holistic view of the relationship between transport infrastructure and Nigeria’s colonial economy before the advent of independence in 1960.